Pelatihan Penggunaan Aplikasi Quizizz Untuk Penilaian Akhir Semester - Khairul Imtihan; Mohammad Taufan Asri Zaen; Hairul Fahmi; Maulana Ashari; Sofiansyah Fadli (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
The role of the teacher in efforts to improve the quality of learning is very much needed, which is in line with the demands of the times that are always developing, and the teacher must also follow the existing demands. Learning technology is currently growing rapidly. Teachers are also starting to change the way of learning by incorporating technology into learning. One way to improve teaching skills is to use up-to-date learning media that students can use through learning applications available on student devices. Paper evaluation sheets for end-of-semester assessments are ineffective and wasteful, and students get bored easily. One application that can be used for learning assessment is Quizizz. Quizizz is an application in the form of an interactive quiz game for online learning. The purpose of this activity is so that participants are able to use Quizizz as a medium for evaluating online learning. Through training on the Quizizz learning application for teachers, they can improve digital literacy for students, which really needs to be developed at this time. The implementation method is through training and mentoring of 22 MTs Jihadul Ummah teachers. Based on the assistance that has been carried out, the result is an increase in the knowledge of 80% of the training participants. This learning app training is very beneficial for teachers who directly impact students in the classroom.